Familiares de dependentes químicos na rede de atenção psicossocial: panorama atual e perfil do grupo - Spagnol, Silvia Campos Brunetti (2018)
This thesis seeks to know the interventions available for caring drug users’ families at Psychosocial Care Network (Rede de Atenção Psicossocial – RAPS) as described in literature. Also, it seeks to identify sociodemographic characteristics, relationship with users, participation in services, as well as identifying and correlating levels of depression, anxiety, codependency, caregiver burden and social skills in a sample of drug users’ relatives at Psychosocial Care Center for Alcohol and other drugs (Centro de Atenção Psicossocial Álcool e Drogas CAPS ad) from Espirito Santo state. For achieving this goal, two studies were developed, one qualitative and other quantitative, in order to cover the response to the phenomenon. At first paper, it was carried out a literature review for identifying and describing interventions with family members at the Alcohol and Drug Psychosocial Attention Network. Search was made on the Portal de Periódicos CAPES, databases PsycINFO, SCIELO, PNAS, PsycArticles and Web of Science, Brazilian Digital Library of Theses and Dissertations (BDTD) and Google Academic, between 2001 and 2016. After reading abstracts and applying the inclusion and exclusion criteria, it was reached the final sample of 22 studies. Second paper was a correlational descriptive study, performed with a sample of 95 drug users’ family members at CAPS ad from Espirito Santo territory, who answered a sociodemographic questionnaire, Beck Depression (BDI) and Beck Anxiety Inventory (BAI), Holyoake Codependency Index (HCI), Zarit Caregiver Burden Interview (BI), and Social Skills Inventory (IHS). Among the main results, it was showed in the study 1 that interventions with family members are offered mainly in CAPS ad, in the form of Family Groups. Some gaps were identified: lack of systematization of the methods that support these groups, necessity of diversification in the form of care, as well as necessity of discussing the theme in academic training and greater investment in training of professionals. Study 2 indicated a profile composed mostly of women, married or in a stable union, 50 years or older and with elementary education. Clinical symptoms of depression (59%); anxiety (55.8%); codependency (40%), burden (57%) and low level of social skills (67%), were detected. There was a significant positive correlation between: depression and anxiety; depression and burden; depression and codependency; anxiety and burden, anxiety and codependency; burden and codependency. There was a negative correlation between depression and social skills and between codependency and social skills. However, there was no significant correlation between anxiety and social skills nor between burden and social skills in this sample. New studies are suggested for a greater contribution on the analyzed phenomena; also, it is important the inclusion of psychological health assessment of family caregivers at RAPS services, as well as the provision of interventions focused on Social Skills acquisition and problem solving strategies, for better supporting the patient's treatment.